Practical aspects of Cu-Mo separations and alternatives to NaSH and Nokes reagent - T. Bhambhani; D. R. Nagaraj; M. Peart; P. Zarate (International Mineral Processing Congress, 2014)
More than 50% of all the molybdenum produced in the world is a by-product of copper production. A bulk Cu-Mo concentrate is first produced, which is subsequently separated into Cu and Mo concentrates. The Cu-Mo separation circuits rely on the use of inorganic Cu sulfide depressants such as NaSH, Na2S, and Nokes, which are hazardous, and sometimes require very large dosages for effective depression. Synthetic polymeric depressants are safer and more efficient, and are now being used on the plant-scale. Data presented in this paper demonstrates that these polymeric depressants can replace 50-90% of all the NaSH in Cu-Mo separation at a fraction of the NaSH dosage. In this paper we provide an overview of the mechanistic and practical aspects of the Cu-Mo separation with inorganic depressants and polymeric depressants. Important practical aspects include depression dynamics (related to conditioning time and rate of depression), optimum pH for effective separation, the role of pH modifiers such as lime and NaOH, and the effect of flotation gas on the efficacy of the separation. Using nitrogen as flotation gas, the NaSH consumption can be reduced by up to 95% by using a small amount of polymeric depressant. The experiments with conditioning time demonstrate that there is a significant rate component to the depression mechanism with NaSH, which is absent for the polymeric depressant system. This has important implications in the effective use and application of the depressant. It is also demonstrated that the pH modifier type (NaOH or Ca(OH)2) has no significant effect on separation efficiency and Mo recovery (i.e. Ca2+ ions do not depress MoS2 in the Cu-Mo separation).